Technology of teaching game techniques in volleyball at the stage of initial training - Doroshenko, E. Yu.; Solovey, O.; Melnyk, M.; Дорошенко, Едуард Юрійович; Соловей, О.; Мельник, М. (My University, 2022)
To scientifically substantiate the method of teaching game techniques at the stage of initial training to increase the level of technical fitness of young volleyball players. The experimental research involved 36 young volleyball players born in 2011 – 18 athletes from the CI “Zaporizhzhia Regional Children and Youth Sports School” of the Zaporizhzhia Regional Council (main group) and 18 athletes from the CI “Vilniansk City Children and Youth Sports School ‘Kolos’” (comparison group) during the 2020-2021 academic year. In the course of experimental research, the indicators of physical fitness of young volleyball players of the main group significantly increased in 80% of tests. The analysis of technical fitness indicators of young volleyball players of the main group shows that the introduction of the author’s method affects their positive dynamics in the tests: consecutive wall passes from a 3 m distance in 30 s; consecutive overhead passes in 30 s; consecutive forearm passes in 30 s; tennis ball toss over the net to the front line; tennis ball toss over the net to the back line (statistically significant differences, if p < 0.05). The author’s method of teaching game techniques in volleyball is effective and contains the algorithm of teaching, the levels of mastering game techniques, the stages of teaching game techniques, the sequence of teaching game techniques, the classification, occurrence and prevention of young volleyball players’ errors in the process of teaching game techniques, differentiation of exercises. Мета – науково обґрунтувати технологію навчання ігровим прийомам на етапі початкової підготовки для підвищення рівня технічної підготовленості юних волейболістів. Матеріали і методи. В експериментальних дослідженнях брали участь 36 юних волейболістів 2011 року народження – 18 спортсменів КЗ «Запорізька обласна дитячо-юнацька спортивна школа» Запорізької обласної ради (основна група) і 18 спортсменів КУ Вільнянська міська дитячо-юнацька спортивна школа «Колос» (порівняльна група) протягом 2020-2021 навчального року. Протягом експериментальних досліджень, показники фізичної підготовленості юних волейболістів основної групи достовірно підвищилися за 80% тестів. Аналіз показників технічної підготовленості юних волейболістів основної групи свідчить, що впровадження авторської технології має вплив на їх позитивну динаміку за тестами: послідовні передачі м’яча у стінку з відстані 3 м за 30 с; послідовні передачі м’яча двома руками зверху над собою за 30 с; послідовні передачі м’яча двома руками знизу над собою за 30 с; метання тенісного м’яча через сітку на переднюю лінію; метання тенісного м’яча через сітку на задню лінію (статистично достовірні розбіжності, при р < 0,05). Авторська технологія навчання ігровим прийомам у волейболі містить алгоритм навчання, рівні засвоєння ігрових прийомів, етапи навчання прийомам техніки гри, послідовність вивчення прийомів техніки гри, класифікацію, виникнення і попередження помилок, які трапляються у процесі навчання ігровим прийомам у юних волейболістів, диференціацію вправ і є ефективною.
Технологія навчання ігровим прийомам у волейболі на етапі початкової підготовки
Doroshenko E. Yu. - https://orcid.org/0000-0001-7624-531X
Keywords: volleyball; method; teaching; ability; skill; волейбол; технологія; навчання; уміння; навичка